Culturing melanocytes and fibroblasts within three-dimensional macroporous PDMS scaffolds: towards skin dressing material - Varshney N.; Sahi A.K.; Vajanthri K.Y.; Poddar S.; Balavigneswaran C.K.; Prabhakar A.; Rao V.; Mahto S.K. (My University, 2025)
In the present study, we propose a platform for topical wound dressing material using a polydimethylsiloxane (PDMS) scaffold in order to enhance the skin healing process. In vitro co-culture assessment of epidermal-origin mouse B16-F10 melanocyte cells and mouse L929 fibroblast cells in three-dimensional polymeric scaffolds has been carried out towards developing bio-stable, interconnected, highly macroporous, PDMS based tissue-engineered scaffolds, using the salt leaching method. To determine a suitable ratio of salt to PDMS pre-polymer in the scaffold, two different samples with ratios 2:1 and 3:1 [w/w], were fabricated. Effective pore sizes of both scaffolds were observed to lie in the desirable range of 152–165 μm. In addition, scaffolds were pre-coated with collagen and investigated as a podium for culturing the chosen cells (fibroblast and melanocyte cells). Experimental results demonstrate not only a high proliferative potential of the skin tissue-specific cells within the fabricated PDMS based scaffolds but also confirm the presence of several other essential attributes such as high interconnectivity, optimum porosity, excellent mechanical strength, gaseous permeability, promising cell compatibility, water absorption capability and desired surface wettability. Therefore, scaffolds facilitate a high degree of cellular adhesion while providing a microenvironment necessary for optimal cellular infiltration and viability. Thus, the outcomes suggest that PDMS based macroporous scaffold can be used as a potential candidate for skin dressing material. In addition, the fabricated PDMS scaffolds may also be exploited for a plethora of other applications in tissue engineering and drug delivery. © 2019, Springer Nature B.V.